RPG Maker MV Game Based on Local Wisdom of Malang Raya to Improve Numeric Literacy - Surayanah, Surayanah; Zainudin, M; Rofiki, Imam; Cahyaningrum, Elaesa Putri Indah; Fikriyah, I'anah El; Ramila, Audiza Assyifa; Lestariningsih, Lestariningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This research was conducted to support numeracy literacy at SDN Lesanpuro 1 Malang which was collaborated with local wisdom in Malang Raya. Based on the results of the needs analysis, the average score of students on the Malang Raya Local Wisdom material was 65 or below standard. The development of media in the form of RPG Maker MV Games is a breakthrough to improve numeracy literacy and knowledge about Local Wisdom in Malang Raya. The objectives of this research are: 1) To produce RPG Maker MV Games based on Malang Raya local wisdom that are practical and valid 2) To develop RPG Maker MV Games that are effective in improving numeracy literacy in Malang Raya local wisdom 3) To find out the improvement in student learning outcomes. The method used in this research is Research and Development (R&D) using the ADDIE development model. The results of this research and development are 1) RPG maker MV game based on local wisdom of Malang Raya with a validity value of 88% for material experts and 100% for media experts 2) The results of teacher practicality are 88.25% with a very practical category and students 73.33% in the practical category 3) Student learning outcomes have increased as evidenced by the results of the pre-test and post-test 0.461 in the moderate category using the N-Gain test.